2018
DOI: 10.4046/trd.2017.0123
|View full text |Cite
|
Sign up to set email alerts
|

CT-Guided Percutaneous Transthoracic Needle Biopsy Using the Additional Laser Guidance System by a Pulmonologist with 2 Years of Experience in CT-Guided Percutaneous Transthoracic Needle Biopsy

Abstract: BackgroundWe developed an additional laser guidance system to improve the efficacy and safety of conventional computed tomography (CT)–guided percutaneous transthoracic needle biopsy (PTNB), and we conducted this study to evaluate the efficacy and safety of our system.MethodsWe retrospectively analyzed the medical records of 244 patients who underwent CT-guided PTNB using our additional laser guidance system from July 1, 2015, to January 20, 2016.ResultsThere were nine false-negative results among the 238 tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
0
9
1
Order By: Relevance
“…As this complicates targeting the lung lesion and may require abandoning the procedure, the result in such cases may be diagnostic failure. Unlike previous studies, we did not find an association between diagnostic failure and male sex, lower lobe location, number of specimens, or a final diagnosis of malignancy [19,23].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As this complicates targeting the lung lesion and may require abandoning the procedure, the result in such cases may be diagnostic failure. Unlike previous studies, we did not find an association between diagnostic failure and male sex, lower lobe location, number of specimens, or a final diagnosis of malignancy [19,23].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have assessed the feasibility and safety of ultrasound-assisted transthoracic biopsy when performed by a pulmonologist [12,13,14,15]. The diagnostic efficacy and safety of CT-guided PTNB using a laser guidance system, performed by a pulmonologist with 2 years of experience in CT-guided PTNB, have also been demonstrated [19]. However, the safety and outcome of CT-guided PTNB performed by an inexperienced pulmonologist had not previously been determined.…”
Section: Discussionmentioning
confidence: 99%
“…It allows to determine the skin puncture site, needle insertion angle, and confirm the needle tip placement. It has been used since the 1980s, and recently published studies showed excellent diagnostic accuracy (96.1%–96.7%) which is comparable to other latest modalities [ 10 - 12 ]. Even the results of CCT-guided TTNB for lesions smaller than 1 cm or ground glass nodule (GGN) showed more than 90% diagnostic accuracy [ 13 ].…”
Section: How To Maximize Diagnostic Accuracymentioning
confidence: 97%
“…It has been used since the 1980s, and recently published studies showed excellent diagnostic accuracy (96.1~96.7%) which is comparable to other latest modalities. [10][11][12][13] Even the results of CCT-guided TTNB for lesions smaller than 1 cm or GGN showed more than 90% diagnostic accuracy. 14 However, there are technical difficulties in patients with large respiratory motion or inability to breathe coordinately due to lack of real-time capability.…”
Section: Conventional Computed Tomography (Cct) Versus Computed Tomogmentioning
confidence: 99%
“…Park HJ, et al Diagnostic tools in lung cancer technique including the addition of laser guidance to improve its accuracy and reduce the risk of complications [26].…”
Section: Transthoracic Needle Aspiration Biopsy With Ct Guidancementioning
confidence: 99%